A conversation about journalism: A role for universities?. Issue 1 (1st June 2023) - Simons, Margaret
Many people would say that journalism is in crisis. In Australia, we regularly see front pages in our newspapers that show scant regard for the facts and are clearly partisan. Two former prime ministers have called for a Royal Commission into the media. Incursions on media freedom are frequent, and Australia has dropped down the scale on measures of media freedom. Meanwhile, repeated attempts to improve self-regulation have created only cynicism. Meanwhile lawyers, doctors and even builders have professional associations in which industry practice and ethics can be discussed. No such body exists for journalists. Social media contains plenty of criticism of journalism, but most are poorly informed and the profession reacts defensively. In this article, I will argue that some of the ideas about journalism that we teach, and measure the profession against, are not as historically well based as we like to think. Journalism has been many things since the profession was created, not all of them good. Now, though, there is the potential for a conversation with the public about what we want journalism to be. What role might universities play in advancing such a conversation? And what outcomes should we seek?